Założeniowość teorii przemian religijności - Sztajer, Sławomir (Polskie Towarzystwo Religioznawcze, 2015)
The article argues that the study of religious change, and especially the theories of secularization, are based on assumptions that influence the way in which theories of religious change are constructed and empirical data are interpreted. Among these assumptions one can find ontological, epistemological, ideological and historiosophical conceptions. An important question is whether such assumptions account for the conceptual and theoretical differences between the current theories of religious change. It can be argued that although the theories of religious change are empirical theories, many of them are based on unempirical assumptions and prompt philosophical reflection on the regularities of religious change.
Keywords: Światopoglądowy charakter sporu o kierunek przemian religijnych; Pokusa wielkich narracji; W poszukiwaniu prawidłowości dziejowych; Pokusa historycyzmu; Założenia historyczne; Co jest przedmiotem badania? Definiowanie i operacjonalizacja pojęć; Wymiar ideowy teorii sekularyzacji; Filozoficzne i teologiczne koncepcje człowieka a teorie przemiany religijności